The Effect of Scissors on Children's Fine Motor Skills - Buana; Pradana, Pascalian Hadi; Ali , A. Zulkarnain; Kurniawan, Nurhafit (Jurusan PG-PAUD Universitas Halu Oleo,, 2024)
Early childhood is a golden period where a child's brain develops and absorbs various things optimally at the same time, so it is an ideal period to lay the foundation for his future life. The aim of this research is to determine the effect of scissors on fine motor skills in young children. The cutting activity is designed to train children's fine motor skills, especially their fingers. The research method used is quantitative research using a single pre-test and post-test group as the research design. The data analysis technique uses a paired sample t-test, one of the test methods used to evaluate the effectiveness of treatment, which characterizes the difference in average values before and after the start of treatment. Based on the research results, in the mandatory test using the normality test and homogeneity test, the sign value for the normality test was 0.200 and the sign value for the homogeneity test was 0.400. In the paired sample test, after the test was carried out, it was found that the sign value was 0.000, where this sign value was less than 0.05. This study concluded that there was an influence of cutting activities on fine motor skills of children.